In vitro antimicrobial screening of Lycoperdon lividum and determination of the ethanol extract composition by gas chromatography/mass spectrometry (Bangladesh Journal of Pharmacology, 2016)
The aim of this study was to investigate the antimicrobial activity of Lycoperdon lividum against 17 bacterial and 1 fungal strains and analyse the composition of ethanol extracts by GC/MS. The in vitro antimicrobial activity of L. lividum extracts having 15 mg/mL concentration was assessed against a wide range of strains by disk diffusion method. The ethanol extract of L. lividum had antimicrobial activity against several microorganism tested, but it was active especially against S. carnosus. The results obtained herein indicate that L. lividum contains several active metabolites.Video clip of Methodology:Disk diffusion test: 7 min 11 sec   Full Screen   Alternate